A scientometric analysis of water resource management research output in sri lanka - Janen, T.; Sivakumar, S.S. (university of Jaffna, 2020)
This paper presents results of the Scientometrics analysis of Water Resource Management research output from Sri Lanka during the period from 1990 to 2019. Research output indexed in Web of Science database. A detailed computational analysis was done and obtained the comprehensive research output, citation impact, collaboration patterns, total research output, citation impact, collaboration patterns, top institutions/authors/publication sources. The analytical results present a detailed and useful picture of status and competence of water resource management domain research in Sri Lanka.
Keywords: water resource management research; informetrics; scientometric; Sri lanka